Fiber Orientation in 3-D Injection Molded Features: Prediction and Experiment - VerWeyst, B. E.; Tucker, C. L.; Foss, P. H.; O'Gara, J. F. (International polymer processing, 1999)
We present a finite element method for predicting the fiber orientation patterns in 3-D injection molded features, and compare the predictions to experiments. The predictions solve the full balance equations of mass, momentum, and energy for a generalized Newtonian fluid. A second-order tensor is used to describe and calculate the local fiber orientation state. A standard Hele-Shaw molding filling simulation is used to provide inlet boundary conditions for the detailed inite element models, which are limited to the local geometry of each feature. The experiments use automated image analysis of polished cross-sections to determine fiber orientation as a function of position. Predictions compare well with experiments on a transverse rib, where the detailed calculation can be 2-D. Results of a 3-D calculation for a flow-direction rib also show generally good agreement with experiments. Some errors in this latter calculation are caused by not simulating the initial filling of the rib, due to computational limits.